A Facile and Universal Top‐Down Method for Preparation of Monodisperse Transition‐Metal Dichalcogenide Nanodots1. (11th March 2015) - Zhang, Xiao; Lai, Zhuangchai; Liu, Zhengdong; Tan, Chaoliang; Huang, Ying; Li, Bing; Zhao, Meiting; Xie, Linghai; Huang, Wei; Zhang, Hua
Abstract Despite unique properties of layered transition‐metal dichalcogenide (TMD) nanosheets, there is still lack of a facile and general strategy for the preparation of TMD nanodots (NDs). Reported herein is the preparation of a series of TMD NDs, including TMD quantum dots (e.g. MoS2, WS2, ReS2, TaS2, MoSe2 and WSe2) and NbSe2 NDs, from their bulk crystals by using a combination of grinding and sonication techniques. These NDs could be easily separated from the N‐methyl‐2‐pyrrolidone when post‐treated with n‐hexane and then chloroform. All the TMD NDs with sizes of less than 10 nm show a narrow size distribution with high dispersity in solution. As a proof‐of‐concept application, memory devices using TMD NDs, for example, MoSe2, WS2, or NbSe2, mixed with polyvinylpyrrolidone as active layers, have been fabricated, which exhibit a nonvolatile write‐once‐read‐many behavior. These high‐quality TMD NDs should have various applications in optoelectronics, solar cells, catalysis, and biomedicine.